Challenges Faced by Learners with Hearing Impairments in a Special School Environment: A Case Study of Embangweni Primary School for the Deaf, Mzimba District, Malawi - Khomera, Sphiwe Wezzie; Fayiah, Moses; Gwayi, Simeon (World Journal of Vocational Education and Training, 2020)
Hearing impairment has been a major disability challenge globally and is considered to a threat to quality education in developing countries like Malawi. This article focuses on the challenges faced by learners with hearing impairments in a special school environment in Malawi. The study was conducted in a selected primary for the deaf in Mzimba District Malawi in 2013. The qualitative research approach was the main method adopted but questionnaires were used to collect basic demographic information about the respondents. The target groups were deaf students, teachers and head teacher of the Embangweni primary school for the deaf. In total, 45 respondents participated in the research (40, students and 5 teachers). The study revealed that students with special needs education are facing multiple challenges such as; shortage of hearing aids, communication barrier with the community surrounding the school, negative attitudes by the community, water supply problem, inadequate funding, abandonment by parents and relatives, shortage of teachers and the lack of transportation facility. These challenges posed both long and short term impact on the academic performance of students attached to the center. This study concludes that disabled students especially those with hearing impairment in rural Malawi are struggling to attain basic education. It is recommended that Malawi government improve financial funding and ensure that basic needed hearing equipment and food supply be made available to all disabled students suffering from hearing impairment. This study serves a baseline for future studies about challenges facing disabled people in Malawi.